Web-based Online Sales - M Zaka; R Yunanto (International Journal of Research and Applied Technology (INJURATECH), 2021)
The purpose of this research is to design an online sales website in the fashion field to increase sales at the Fashionku store. The research method used a waterfall method by observing and designing a web-based system, which uses the help of XAMPP software as well as analytical tools using PHP, HTML, and CSS. The research results show that website design for Fashionku online sales. The existence of online websites for Fashionku stores is expected to increase sales. Product innovation, distribution of advertisements, and website appearance with complete features are things that will attract the attention of customers to buy products